If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2x+1/3)+(5x+2/3)=(12x-4)
We move all terms to the left:
(2x+1/3)+(5x+2/3)-((12x-4))=0
We add all the numbers together, and all the variables
(+2x+1/3)+(+5x+2/3)-((12x-4))=0
We get rid of parentheses
2x+5x-((12x-4))+1/3+2/3=0
We multiply all the terms by the denominator
2x*3+5x*3-(((12x-4)))*3+1+2=0
We add all the numbers together, and all the variables
2x*3+5x*3-(((12x-4)))*3+3=0
Wy multiply elements
6x+15x-(((12x-4)))*3+3=0
We add all the numbers together, and all the variables
21x-(((12x-4)))*3+3=0
We move all terms containing x to the left, all other terms to the right
21x-(((12x-4)))*3=-3
| 7v/11-19/14=11/2-5v/8 | | 5n+17=-3(1-5n) | | 3x-18=5x5 | | 3=-3p+2p | | x-0.1x=315000 | | 7/9b=49 | | x^2+5=51/16 | | 0.83*x=40 | | (.4)x=3500 | | y-1=5(+2) | | 7=1-4a+2 | | 0.4(x+3)-6(2x-4)=-3.8 | | -4y+7(-5y-2)=8-1(-5-y) | | -8x-7=5x=29 | | -12m-6=66 | | 8x-4=3x+9 | | 7y-2y+4+3y=97 | | 2(w+2)=6w-32 | | B=21+-3b | | 3x+6=175 | | 80x-150=2x+1 | | 15+22+5x=2 | | 6m-9=11m | | 8x-5x=15+2x | | -9v-39=3(v+7) | | 49=81v^2 | | -2y-1(-7y+3)=1+2(-1-y) | | n-19=-2n+20 | | 27-6=6x | | 20=30/(y-10) | | 8a-3=6a-15 | | 15/21=x/3 |